Critical community psychology critical action and social change - Kagan, Carolyn; Burton, Mark (Mark H.) 1952-; Duckett, Paul; Lawthom, Rebecca 1968-; Siddiquee, Asiya (Routledge, an imprint of the Taylor & Francis Group, 2020)
This accessible textbook draws upon progressions in academic, political and global arenas, to provide a comprehensive overview of practical issues in psychological work across a diverse range of community settings. Interest in community psychology, and its potential as a distinctive approach, is growing and evolving in parallel with societal and policy changes. Thoroughly revised and updated, this new edition covers crucial issues including decolonial approaches, migration, social justice, and the environmental crisis. It has a new chapter on archive research, working with data, policy analysis and development, to reflect the continuously developing global nature of community psychology. Key features include: Sections and chapters organised around thinking, acting and reflecting Case examples and reflections of community psychology in action Discussion points and ideas for exercises that can be undertaken by the reader, in order to extend critical understanding Aiming to provide readers with not only the theories, values and principles of community psychology, but also with the practical guidance that will underpin their community psychological work, this is the ideal resource for any student of community, social, and clinical psychology, social work, community practice, and people working in community-based professions and applied settings.